KAJIAN KINERJA KONSULTAN SUPERVISI PROYEK KONSTRUKSI JALAN DI WILAYAH ACEH - Taufik Prawira Hidayah; Anton Soekiman (Center for Research and Community Service (LPPM) University of Abulyatama, 2015)
This study was conducted to analyze the factors that most affect the performance and how’s performance Supervision Consultant in Aceh region. Respondents in this study amounted to 75 people consisting of supervising consultant residing in Aceh region . Testing the hypothesis in the research done by using path analysis. Descriptive analysis results of this study showing the supervising consultant's performance in Aceh region is good with a mean total of 3.7826, the effect of each variable and a significant variable or the most influence with the performance of a supervision consultant is education variable (X1) with a value of 3%, training variable (X2) with a value of 7.37%, skill variable (X3) with a value of 4.45%, experience variable (X4) with a value of 1.78%, incentive variable (X5) with a value of 0.01%, salary variable (Y1) with a value of 14.9%, motivation variable (Y2) with a value of 0.09% and a salary variable (Y1) through Training (X2) with value of 11.1%, a salary variable (Y1) through